Production and application method for biological liquid selenium fertilizer containing molasses liquid - QIN JIANZHONG (2017)
The invention relates to selenium fertilizer containing molasses liquid and belongs to the technical field of production of biological liquid fertilizer. The selenium fertilizer containing the molasses liquid is prepared from molasses liquid, selenium fertilizer, amino acid, zinc sulfate, boron fertilizer, ammonium molybdate and water. The biological liquid selenium fertilizer containing the molasses liquid is applied to production of animals and plants, the product has unique fragrant and sweet smells, and diet palatability and food intake of a ruminant animal can be effectively improved, so that the animal can obtain more balanced and adequate nutrition, photosynthetic efficiency of a plant can be improved, growth is promoted, absorption is enhanced, and yield and selenium content of the product are increased. 种含糖蜜液硒肥，属于生物液体肥生产技术领域，由糖蜜液、硒肥、氨基酸、硫酸锌、硼肥与钼酸铵、水组成；本发明的种含糖蜜液的生物液体硒肥应用于动植物生产，产品有其独特的甜香气味，可以有效改善反刍动物日粮的适口性与进食，使动物能够获得更加均衡充足的营养，能提高植物光合效率，促进生长，增强吸收，增加产量与产品含硒量。